Institutional ownership and earnings management: Evidence from India - Srikanth Potharla; Kaushik Bhattacharjee; Vishwanathan Iyer (Cogent Economics & Finance, 2021)
The present study analyzes and assesses the robustness of monitoring effectiveness of institutional investment against the information asymmetry prevailing in the market, especially the asymmetric monitoring effectiveness of Domestic Institutional Investment (DII) vis-à-vis Foreign Institutional Investment (FII). Drawing from a sample of listed non-financial firms with institutional investment of 20% or more, this study tests the relationship between earnings management and institutional ownership controlling for known firm-specific variables. The results reveal that institutional investment in aggregate as well as DII and FII have significant negative impact on earnings management supporting the active monitoring hypothesis. The results also support hometown advantage hypothesis for the sub-group of companies with higher Price to Book Value (PBV) and global investor hypothesis for the sub-group of companies with lower PBV ratio. Various implications applicable in the Indian markets contexts are discussed. Domestic institutional investors should improve their cost-effective technology to acquire and process the price-sensitive information which can enhance their competitive advantage over their foreign counterparts. This is one among the first few studies that tests the robustness of monitoring effectiveness of institutional investment against the information asymmetry in the market and shows that monitoring effectiveness of FII and DII is not uniform across companies in which they invest. Another contribution to the extant literature in India is the analysis using alternative definitions of earnings management, incorporating industry-specific and time-specific factors in estimation of discretionary accruals.
Keywords: 330; Active Monitoring Hypothesis; earnings management; Global Investor Hypothesis; Home Town Advantage Hypothesis; India; Institutional ownership